2015
DOI: 10.1021/acsami.5b02226
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Surface Chemistry and Topologic Structure from Modified Microarc Oxidation Coatings on Ti Implants for Improving Osseointegration

Abstract: Microarc oxidation (MAO) coating containing Ca, P, Si, and Na elements on a titanium (Ti) implant has been steam-hydrothermally treated and further mediated by post-heat treatment to overcome the compromised bone-implant integration. The bone regeneration, bone-implant contact, and biomechanical push-out force of the modified Ti implants are discussed thoroughly in this work. The best in vivo performances for the steam-hydrothermally treated one is attributed to the synergistic effects of surface chemistry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 56 publications
1
49
0
1
Order By: Relevance
“…The biomaterial surface properties of an implanted medical device have demonstrated to contribute to the host cellular and tissue responses and play a significant role in determining the overall implant success or failure. 9 , 10 Therefore, manipulating the surface physical or chemical properties offers an effective and straightforward strategy to improve the biological performance of implant materials. For titanium implants installed in bone defects in animal studies, multiple studies have shown superior bone-to-implant contact and peri-implant bone formation when the surface roughness (arithmetical mean deviation of the surface profile, R a ) is between 1 and 1.5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The biomaterial surface properties of an implanted medical device have demonstrated to contribute to the host cellular and tissue responses and play a significant role in determining the overall implant success or failure. 9 , 10 Therefore, manipulating the surface physical or chemical properties offers an effective and straightforward strategy to improve the biological performance of implant materials. For titanium implants installed in bone defects in animal studies, multiple studies have shown superior bone-to-implant contact and peri-implant bone formation when the surface roughness (arithmetical mean deviation of the surface profile, R a ) is between 1 and 1.5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Material and device design explored together yielded a breakthrough advancement in the form of hydroxyapatite (HA) through a myriad of device designs beyond the scope of this manuscript (Barber et al, 1998; Facca et al, 2011; McAfee et al, 2003; Nepal et al, 2014; Salou et al, 2015; Sandén et al, 2002; Spivak and Hasharoni, 2001; Yerby et al, 1998; Yildirim et al, 2006; Zhou et al, 2014, 2015). The subject of improving osseointegration following initial surgical placement is paramount as it will ensure long lasting surgical hardware stability.…”
Section: Introductionmentioning
confidence: 99%
“…Combined previous reports 2730 with the results in Figs 1 and 2, formation process of HTO can be analyzed as follows. During HT process, Ti-O-Ti bonds initially dissolve due to the attack of OH −   27,29 , following the reaction: TiO 2  + OH −  → HTiO 3 − . Then, HTiO 3 − reacts with TiO 2 and H 2 O to form HTO nuclei: 3TiO 2  + 2HTiO 3 −  + 2H 2 O → H 2 Ti 5 O 11 ·H 2 O + 2OH − .…”
Section: Discussionmentioning
confidence: 93%